Philosophy for Education: Towards Human Agency - Bai, Heesoon (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
This paper considers the contribution of philosophy to education. First, a case is made that the fundamental goal of education is to cultivate human agency in the sense of being able to enact one’s freedom (as opposed to conditioned and habituated patterns of thinking, perception, and action) grounded in personal knowledge and ethics. This agency is named as ‘autonomy’ in this paper. Secondly, philosophy is conceived as an “art of living,” which has ancient roots in both the East and West. An argument is made that identifying philosophical activity as predominantly discursive and theoretical activity entrenches us in the “addiction” to conceptualization and blinds us to seeing that a map is not the territory. Human beings encompass the discursive as well as the non-discursive, theoretical as well as practical dimensions. Hence philosophy as an art of living must address all the dimensions. As an illustration, a number of exemplary philosophic arts pertaining to these practices are explored, including world-making through dialogue (Socratic); autobiographical experiment through philosophical writing (Nietzschean); human-making and self-transformation (Confucian); and mindfulness practice (Buddhist). The case is made that these practices combine to illustrate and demonstrate that philosophy is a practice devoted to the cultivation of fundamental human agency, namely autonomy.